Spondyloocular Syndrome: A Novel XYLT2 Variant with Description of the Neonatal Phenotype - Doddato, Gabriella; Fabbiani, Alessandra; Fallerini, Chiara; Bruttini, Mirella; Hadjistilianou, Theodora; Landi, Martino; Coradeschi, Caterina; Grosso, Salvatore; Tomasini, Barbara; Mencarelli, Maria Antonietta; Renieri, Alessandra; Ariani, Francesca (Frontiers in Genetics, 2021)
Spondyloocular syndrome (SOS) is a skeletal disorder caused by pathogenic variants in XYLT2 gene encoding a xylotransferase involved in the biosynthesis of proteoglycans. This condition, with autosomal recessive inheritance, has a high phenotypic variability. It is characterized by bone abnormalities (osteoporosis, fractures), eye and cardiac defects, hearing impairment and varying degrees of developmental delay. Until now only 20 mutated individuals have been reported worldwide. Here, we describe two siblings from consanguineous healthy parents in which a novel homozygous frameshift variant c.1586dupG (p.(Thr530Hisfs*)) in the XYLT2 gene was detected by exome sequencing (ES). The first patient (9 years) presented short stature with skeletal defects, long face, hearing loss and cataract. The second patient, evaluated at a few days of life, showed macrosomia, diffuse hypertrichosis on the back, overabundant skin in the retronucal area, flattened facial profile with drooping cheeks, elongated eyelid rims, wide and flattened nasal bridge, turned down corners of the mouth. During the prenatal period, high nuchal translucency and intestinal hyperechogenicity were observed at ultrasound. In conclusion, these two siblings with a novel pathogenic variant in XYLT2 further expand the clinical and mutational spectrum of SOS.